TECHNICAL AND ECONOMIC OPTIMUM FERTILIZER APPLICATION RATES FOR SELECTED CEREALS AMONG SMALLHOLDER FARMERS IN BENUE STATE, NIGERIA - Iheanacho, A.C.; Okeke, A.M.; Aker, I.E. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study determined the technical and economic optimum fertilizer application rates for selected cereals among smallholder farmers in Benue State, Nigeria. Multistage sampling procedure was used to select 120 respondents. Data were collected using structured questionnaire and analysed using production function and multiple regression analysis. The production function analysis reveals that the current fertilizer application rate by the farmers for maize, millet, rice, and sorghum production were 42.89, 63.63, 53.47, and 43.75kg/ha respectively. The technical optimum fertilizer rate for maize, millet, rice, and sorghum production were 94.40, 440.53, 415.44, and 224.24kg/ha respectively while the economic optimum fertilizer rate for maize, millet, rice, and sorghum production were 94.35, 438.77, 413.91, and 222.38kg/ha respectively. The multiple regression results on the determinants of fertilizer use show that household size, age, and farm size of these farmers significantly influence their use of inorganic fertilizer in cereal production. The multiple regression results further show that these farmers’ access to credit and membership to cooperative significantly influence their use of inorganic fertilizer in cereal production. The study concludes that gap exist between the current fertilizer application regime of these farmers and the optimum rates, and that their use of fertilizer is influenced by their socio-economic characteristics. It was recommended that the Benue State Ministry of Agriculture should organize training workshops where experts in fertilizer application will be invited to train the farmers on optimum application rates; and Benue State Government should establish and fund community Farmer Field Schools to deliver season-long practical training on fertilizer usage.